Ethno-Religious Struggle and Human Insecurity in the Fledging Nigerian Democracy since 1999: The Political Nexus - Eze, Malachy Chukwuemeka (Society & Sustainability, 2021)
Religious and ethnic identity clashes laid the structure of the Nigerian state in 1914, which transmogrified into and characterized the struggle for control of power and distribution of national resources. This paper explores the nature and manifestation of these conflicts since 1999. It seeks to find out if ethno-religious struggles led to the emergence of major conflicts in Nigeria since 1999, their impact on human insecurity, and the influence of politics on the conflicts. This inquiry is designed in line with a one-shot case study, while literature survey and ex post facto methods were adopted as methods of data collection. Trend analysis is adopted for data analysis. Analysis reveals that ethno-religious struggles were the primary progenitor of conflicts in Nigeria since 1999, and have debilitating consequences while politics exacerbated ethno-religious conflicts. Upholding Nigeria's circular state and implementing the National Political Reforms Conference Report is the panacea for ethno-religious conflicts in Nigeria.